Physics in Oxford, 1839-1939 : Laboratories, Learning and College Life. - Fox, Robert (Oxford University Press, UK, 2005)
This book shows that physics in pre-war Oxford has a colourful and dynamic history. Its examination of physics teaching and research in the University's constituent colleges reveals a unique world that helped to make Oxford physics in the twentieth century a force to rival that of the Cavendish Laboratory at Cambridge. - ;Physics in Oxford, 1839-1939 offers a challenging new interpretation of pre-war physics at the University of Oxford, which was far more dynamic than most historians and physicists have been prepared to believe. It explains, on the one hand, how attempts to develop the Univers.